2014
DOI: 10.1124/jpet.114.218180
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate-Mediated Upregulation of the Multidrug Resistance Protein 2 in Porcine and Human Brain Capillaries

Abstract: As a member of the multidrug-resistance associated protein (MRP) family, MRP2 affects the brain entry of different endogenous and exogenous compounds. Considering the role of this transporter at the blood-brain barrier, the regulation is of particular interest. However, there is limited knowledge regarding the factors that regulate MRP2 in neurologic disease states. Thus, we addressed the hypothesis that MRP2 might be affected by a glutamateinduced signaling pathway that we previously identified as one key mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…112,116 This may be due to low basal expression of Mrp2, which may be upregulated in response to cellular stressors such as oxidative stress. 117,118 In mice, there are notable differences in Mrp expression between strains and between vessels of different diameters. For example, Friend virus B (FVB) mice appear to lack Mrp2 in brain vessels, but it is present in C57BL/6 and Swiss mice.…”
Section: Bbb Protection In Ischemic Strokementioning
confidence: 99%
“…112,116 This may be due to low basal expression of Mrp2, which may be upregulated in response to cellular stressors such as oxidative stress. 117,118 In mice, there are notable differences in Mrp expression between strains and between vessels of different diameters. For example, Friend virus B (FVB) mice appear to lack Mrp2 in brain vessels, but it is present in C57BL/6 and Swiss mice.…”
Section: Bbb Protection In Ischemic Strokementioning
confidence: 99%
“…In similar study, the same group showed that MRP2 expression and activity increased significantly in porcine and human BBB models after exposure to glutamate. The NMDA/COX-2 cascade was shown to be involved (Luna-Munguia et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…For OAT and P-gp an apical and sub-apical localization was stated, whereas MRP1 was demonstrated to be expressed at the basolateral membrane. 36,37 Indomethacin as substrate for OAT2 and the MRP family, 22,23 valspodar representing a P-gp inhibitor 38 and fumitremorgin C as ABCG2 inhibitor 39 did not inhibit the efflux of organic mercury compounds out of the brain. In the rat choroid plexus, LAT1 has been demonstrated to be localized at the basolateral membrane 29,30 and thus further studies could prove whether LAT1 is also localized on the basolateral membrane of the applied primary porcine blood-CSF barrier model and might contribute to the observed efflux of the organic mercury compounds in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Fumitremorgin C (498% purity) was used to inhibit the ATP binding cassette (ABC)-transporter G2 (ABCG2), PSC 833 (valspodar, 498% purity) to inhibit P-glycoprotein (P-gp/ABCB1) and indomethacin (499% purity, all Sigma Aldrich) to inhibit organic anion transporter 2 (OAT2) and/or multidrug resistance associated protein (MRP), respectively. [21][22][23] The stock solutions of the respective inhibitors were prepared in dimethyl sulfoxide (DMSO, Roth, Karlsruhe, Germany) and applied in the apical as well as in the basolateral compartment simultaneously with a final inhibitor concentration of 10 mM 1 h before treatment with the mercury compounds on both sides (1 mM). The DMSO concentration did not exceed a concentration of 1% in the wells.…”
Section: Cytotoxicity Testingmentioning
confidence: 99%